STRATEGI PERGURUAN TINGGI MEMAJUKAN LEMBAGA KEUANGAN SYARIAH - Ibda, Hamidulloh (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2018)
This article discusses the university’s strategy in advancing Islamic Financial Institutions to responding the challenges of the Fourth Industrial Revolution era. In addition to having new literacy skills, Islamic economics students and scholars are required to master 21st century competencies. The method of writing this article uses a descriptive qualitative approach that refers to library research. From the results of the discussion, the university’s strategy in advancing sharia financial institutions is divided into long and short term. In the long run, universities prepare quality human resources. First, strengthening the curriculum refers to KKNI-SNPT. Second, the contextual learning orientation in the field, especially in Islamic economics / economics study programs in collaboration with Islamic financial institutions. Third, the synergy of the Financial Services Authority and Islamic Financial Institutions in strengthening training for sharia financial trainers. Fourth, cooperation in sharia financial institutions or financial institutions abroad. In short, tertiary institutions apply financial literacy to students to increase inclusion of Islamic finance. First, strengthening financial literacy in the real action area. Second, strengthening new literacy-based financial literacy that targets data literacy, technology and human literacy capabilities. Third, increase activities in the form of socialization, seminars, public lectures, or field-based practices that combine collaboration between the campus, the Financial Services Authority, Islamic Financial Institutions, and related agencies. Fourth, research-based innovation on sharia economic products that are rarely addressed. For example sharia tourism (nature, religion, culinary, cultural), e-commerce, and others. Fifth, patent and continuous collaboration between universities and Islamic Financial Institutions by making “student savings”. Sixth, educational scholarships or educational loans are products of the Islamic Financial Institutions itself.